Navigating Stock Analysis with Artificial Intelligence: An Islamic Economic Approach to Mitigate Gharar and Maysir - Muhammad Rani; Muhammad Siraz; Mawar Ardiyansah; Rahmad Fahreza Setiawan; Wahyu Akbar (Muttaqien, 2026)
The increasing interest of Indonesian people in stock investment, especially sharia stocks, drives the need for careful analysis in accordance with Islamic principles. On the other hand, the development of Artificial Intelligence (AI) technology offers great potential in capital market analysis, but the lack of in-depth research raises questions about its suitability with sharia principles. This study uses a qualitative descriptive methodology with a literature review approach, collecting data from various secondary sources such as journal articles, books, and relevant online publications. This study aims to: (1) examine stock analysis from an Islamic economic perspective, (2) analyze the role of AI as a stock analysis tool, and (3) explore the Islamic economic perspective on AI-based stock analysis. The results indicate that AI has the potential to improve the efficiency and accuracy of Islamic stock analysis. However, investors must carefully identify and understand the characteristics of the AI used to prevent the practices of gharar (uncertainty) and maysir (excessive speculation). This study is important in a multidisciplinary context because it bridges the latest technological developments with the principles of Islamic economics, providing ethical and practical guidance for Muslim investors in the digital era.